Identifikasi Spesies Pohon di Wilayah Kampus UNM Parang Tambung - Syamsiah Syamsiah; Muhammad Junda; Ifka Ikbal (bionature, 2022)
Abstract. UNM Parang Tambung applies the concept of a comfortable and breathaking environment. Various types of trees have grown since the campus was founded, yet several were deliberately planted in open land. Plants have different categories of main benefits, one of the benefits applied here that is the presence of various types of trees and other plants in campus environment. The purpose of the study was to determine the types of trees that grow in UNM Parang Tambung. The research method used is descriptive qualitative, this research was carried out by systematically describing data about the characteristics of tree plants in UNM Parang Tambung campus area. The results showed that there were 956 individual trees consisting of 34 species belonging to 20 families. The species are Alstonia scholaris, Araucaria heterophylla, Artocarpus altilis, Artocarpus heterophyllus, Averrhoa bilimbi L, Cocos nucifera, Delonix regia Raf, Dimocarpus longan Lour, Ficus benjamina L, Ficus septica Burm F, Gmelina arborea, Guazoma ulmifolia Lamk, Livistona saribus, Mangifera indica, Mimusops elengi L, Morinda citrifolia L., Moringa oleifera, Muntingia calabura L, Paraserianthes falcataria, Plumeria rubra, Polyalthia longifolia, Pterocarpus indicus Willd, Ptychosperma macarthurii, Roystone regia, Samanea saman, Senna siamea, Spatodea campanulata P.B, Switenia mahagoni, Syzygium aqueum, Syzygium cumini, Tectona grandis, Terminalia catappa, Terminalia mantaly, and Wodyetia bifurcata L.Keywords: unm campus, tree, identification, parang tambung